Ответы и объяснения

2014-01-20T14:18:21+04:00
X²+8x=0
x(x+8)=0
x=0  x+8=0
         x=-8

(2x+1)(x-3)=x(3+2x)
2x²+x-6x-3-3x-2x²=0
-8x=3
x=-3/8
  • Участник Знаний
2014-01-20T14:18:50+04:00
X^2 + 8X = 0
X*( X + 8 ) = 0
X = 0
X + 8 = 0 ---> X = ( - 8 )
Ответ 0 и ( - 8 ) 
.....................................................
(2Х +1 ) * ( Х - 3 ) = X * ( 3 + 2X )
2X^2 - 6X + X - 3 = 3X + 2X^2 
2X^2 - 5X - 3 = 2X^2 + 3X 
2X^2 - 2X^2 - 5X - 3X - 3 = 0
- 8X - 3 = 0
8X = - 3 
X = ( - 3\8 ) = ( - 0.375 )
ОТВЕТ: ( - 0.375 )